2015
DOI: 10.1245/s10434-015-4609-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Number Versus Ratio of Positive Lymph Nodes in the Assessment of Lymph Node Status in Extrahepatic Cholangiocarcinoma

Abstract: The number of positive lymph nodes predicts survival better than the LNR after resection of extrahepatic cholangiocarcinoma, provided that nodal evaluation is sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The coefficients of correlation and corresponding p values are listed in Supplementary Table . Lymph nodes status is a strong determinant of clinical outcomes for patients with various gastrointestinal cancers . Intriguingly, we noticed that a branching fucosylated triantennary N ‐glycan (peak9, AUC = 0.845) and a branching fucosylated tetra‐antennary N ‐glycan (peak12, AUC = 0.761) were positively correlated with lymph node involvement ( p < 0.05), whereas CA19‐9, the commonly used marker, was not related to this pathological feature.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The coefficients of correlation and corresponding p values are listed in Supplementary Table . Lymph nodes status is a strong determinant of clinical outcomes for patients with various gastrointestinal cancers . Intriguingly, we noticed that a branching fucosylated triantennary N ‐glycan (peak9, AUC = 0.845) and a branching fucosylated tetra‐antennary N ‐glycan (peak12, AUC = 0.761) were positively correlated with lymph node involvement ( p < 0.05), whereas CA19‐9, the commonly used marker, was not related to this pathological feature.…”
Section: Resultsmentioning
confidence: 79%
“…As is well‐known, assessment of nodal status might harbor important prognostic information and guided adjuvant treatment . Correlation analyses and ROC curves indicated that a branching fucosylated triantennary N ‐glycan (peak9) and branching fucosylated tetra‐antennary N ‐glycan (peak12) were closely related with lymph metastasis.…”
Section: Discussionmentioning
confidence: 92%
“…Substantial number of lymph nodes, resection is justified for appropriate staging of nodal ailment. We firmly assume that comprehensive localized lymphadenectomy definitely seems to be required for effective resection of extrahepatic cholangiocarcinoma [62].…”
Section: Surgical Resectionmentioning
confidence: 79%
“…In PHC, most often concomitant vascular resections and reconstruction are needed in order to achieve the negative margin. Our latest research implies that count of positive lymph nodes much better anticipates survival following surgical resection compared to lymph node resection in extrahepatic cholangiocarcinoma, given that lymph node assessment is enough [62]. Substantial number of lymph nodes, resection is justified for appropriate staging of nodal ailment.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…In addition to some conventional demographic and clinicopathological factors, such as age, gender, tumor location, tumor differentiation, T and N staging, etc., the veri ed cancer-related prognostic factors, including Albumin to globulin ratio (AGR), Neutrophil to lymphocyte ratio (NLR), Platelet to lymphocyte ratio (PLR), Positive lymph nodes ratio (PRL), Low-density lipoprotein (LDL), and Prognostic Nutritional Index (PNI) are candidates of nomogram establishment. (25,26) Among them, six factors including age, gender, N stage (with modi ed), AGR, PRL, PNI were identi ed as independent prognostic factors by statistical Cox hazard regression analysis, and the Hazard Ratio (HR) of each factor displays the weight of score in the nomogram. (9) For demographic characteristics, we found that two factors, age and gender, were associated with OS of EC patients after radical esophagectomy, and thus were included into the establishment of nomogram.…”
Section: Roc Of Nomogram In Prediction Os Compared With Ajcc T Stage mentioning
confidence: 99%